2000
DOI: 10.4269/ajtmh.2000.62.151
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of the yellow fever virus by Aedes aegypti (Diptera, Culicidae): dynamics of infection in F1 adult progeny of orally infected females.

Abstract: Abstract. Vertical transmission of yellow fever virus from orally infected females to their progeny was experimentally demonstrated in 2 Aedes aegypti colonies from the Dakar and Koungheul regions in Senegal. A total of 10,530 F 1 adult mosquito progeny were tested. The overall vertical transmission rate was 0.97%, with no significant difference between the Dakar and Koungheul colonies. The infection rates were significantly higher in females (1.15%) than in males (0.74%) in both colonies. The virus was not is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 22 publications
3
35
0
1
Order By: Relevance
“…The expansion of the ovaries during oogenesis may also increase the permeability of tissue to virus, contributing to increased VT in subsequent cycles [103]. Absence of virus in the first gonotrophic cycle has been observed for chikungunya virus (Alphavirus), [103] and YFV [104]. This contrasts with the detection of LACV and CEV in the progeny of Aedes spp.…”
Section: Ovarian Cyclementioning
confidence: 99%
“…The expansion of the ovaries during oogenesis may also increase the permeability of tissue to virus, contributing to increased VT in subsequent cycles [103]. Absence of virus in the first gonotrophic cycle has been observed for chikungunya virus (Alphavirus), [103] and YFV [104]. This contrasts with the detection of LACV and CEV in the progeny of Aedes spp.…”
Section: Ovarian Cyclementioning
confidence: 99%
“…(iii) There is evidence of vertical transmission in mosquitoes in Senegal, where YFV has been isolated from male Aedes furcifer-taylori (8) and A. aegypti (12,20) mosquitoes. Transovarial transmission has also been reported for Haemagogus equinus (17) and Aedes sp.…”
mentioning
confidence: 99%
“…This result was expected because urban transmission of this virus has not been reported in Brazil since 1942. One study conducted in Senegal reported transovarial infection with a MIR of 0.97% in adults emerging from the eggs of females experimentally infected through the oral route (50) .…”
Section: Discussionmentioning
confidence: 99%